Odpowiedź :
9.
a)
[tex] \frac{4}{ \sqrt{2} } = \frac{4 \times \sqrt{2} }{ \sqrt{2 \times \sqrt{2} } } = \frac{4 \sqrt{2} }{ \sqrt{4} } = \frac{4 \sqrt{2} }{2} = 2 \sqrt{2} [/tex]
b)
[tex] \frac{3}{2 \sqrt{2} } = \frac{3 \sqrt{2} }{4} = \frac{3}{4} \sqrt{2} [/tex]
c)
[tex] \frac{4}{ \sqrt{3} } = \frac{4 \sqrt{3} }{3} = 1 \frac{1}{3} \sqrt{3} [/tex]
d)
[tex] \frac{6}{5 \sqrt{3} } = \frac{6 \sqrt{3} }{15} = \frac{2}{5} \sqrt{3} [/tex]
10.
a)
Pole
[tex] \sqrt{2} \times 3 \sqrt{2} = 3 \sqrt{4} = 3 \times 2 = 6[/tex]
Obwód
[tex] \sqrt{2} + \sqrt{2} + 3 \sqrt{2} + 3 \sqrt{2 } = 8 \sqrt{2} [/tex]
b)
Pole
[tex] \sqrt{3} \times \sqrt{12} = \sqrt{48} = \sqrt{16 \times 3} = 4 \sqrt{3} [/tex]
Obwód
[tex] \sqrt{3} + \sqrt{3} + \sqrt{12} + \sqrt{12} = 2 \sqrt{3} + \sqrt{4 \times 3} + \sqrt{4 \times 3} = 2 \sqrt{3} + 2 \sqrt{3} + 2 \sqrt{3} = 6 \sqrt{3} [/tex]
Myślę że pomogłem ;)